Analysis of Skin Disorders Among Traditional Fishermen in Tanjung Balai, Asahan District - Aynil Paydah Harahap; Umi Salmah; Eka Lestari Mahyuni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Skin disorders are diseases often found in the community caused by fungi, bacteria, viruses, and marine life characterized by rashes, itching, and others. Traditional fishermen are a group of people at high risk of skin disorders due to exposure to seawater, unhygienic working environment conditions, incomplete behaviour of using fishermen's protective equipment when working and personal hygiene behaviour classified as harmful. This study aims to analyze skin disorders among traditional fishermen in Tanjung Balai, Asahan District. The research employs a quantitative, analytical survey with a cross-sectional design. The study was conducted in Tanjung Balai, Asahan District, from August 2023 to March 2024. The research population consisted of all traditional fishermen, totalling 110, 110 traditional fishermen, with the sample taken based on the total population of 110 fishermen in Tanjung Balai, Asahan District. The sampling technique used was total sampling. Data collection was conducted using using questionnaires that have been tested for validity, reliability, and observation. Data analysis involved two steps: univariate analysis using descriptive statistics and frequencies and bivariate analysis using the chi-square test with a significance level of 95% (p-value ≤ 0.05). The statistical analysis results indicated significant associations between skin disorders and factors such as duration of work (p=0.001), use of personal protective equipment (p=0.038), and fishermen's hygiene (p=0.014). It is recommended that traditional fishermen use complete personal protective equipment and maintain better personal hygiene after working to prevent the occurrence of skin disorders. Keywords: Skin disorders, traditional fishermen